Household livelihood diversification in rural Africa - Musumba, M.; Palm, C.A.; Komarek, A.M.; Mutuo, P.; Kaya, B. (Wiley, 2022)
Diversification is a common livelihood strategy for rural households in developing countries, with diversification being either a choice or necessity depending on individual household contexts. Using two waves of data (from 2009 and 2011) for 1773 households from eight countries in sub-Saharan Africa, we examined livelihood diversification and its drivers. We examined livelihood diversification by considering household involvement in three livelihood activities: crop, livestock, and non-farm. Results indicated that 40% of households conducted all three livelihood activities, but there was heterogeneity in diversity levels. We used a correlated random effects model to identify the factors that pushed or pulled households to diversify their activities. Access to non-agricultural credit was positively associated with livelihood diversity as it can catalyze involvement in non-farm activities. Drought had a negative effect on livelihood diversity. Area of crop land had a positive effect on the number of livelihood activities conducted. We found that 53% of households added or removed at least one livelihood activity between 2009 and 2011, and the addition of non-farm activities was the most common change. Our results demonstrated the dynamic nature of livelihoods and importance of shocks (such as drought) and resource endowments (land) in understanding household livelihood diversification.